2022
DOI: 10.1093/intbio/zyac014
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered and functionalized silk proteins accelerate wound healing in rat and human dermal fibroblasts

Abstract: Wound healing is an intrinsic process directed towards the restoration of damaged or lost tissue. The development of a dressing material having the ability to control the multiple aspects of the wound environment would be an ideal strategy to improve wound healing. Though natural silk proteins, fibroin, and sericin have demonstrated tissue regenerative properties, the efficacy of bioengineered silk proteins on wound healing is seldom assessed. Furthermore, silk proteins sans contaminants, having low molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The results of wound healing assays (figure 2) indicated that the mixture was more effective in wound healing than sericin alone. After 12 days, the wound recovery ratio of the EW + S-M group reached the highest (87.1%), which was a little lower than it of the wound treated with recombinant sericin-cecropin B (93%) reported by Manoharan et al [46]. Our result was also similar to it of wound treated with lysozyme separated from EW.…”
Section: Discussionsupporting
confidence: 79%
“…The results of wound healing assays (figure 2) indicated that the mixture was more effective in wound healing than sericin alone. After 12 days, the wound recovery ratio of the EW + S-M group reached the highest (87.1%), which was a little lower than it of the wound treated with recombinant sericin-cecropin B (93%) reported by Manoharan et al [46]. Our result was also similar to it of wound treated with lysozyme separated from EW.…”
Section: Discussionsupporting
confidence: 79%
“…Bacterial metabolites can also cause leukocyte dysfunction [ 9 ], which inhibits migration of epidermal cells and keratinocytes [ 10 ]. For the treated group with SS-based antimicrobial dressing, pathogenic bacteria proliferation was significantly inhibited and it can promote wound healing through hemostasis, anti-inflammation, cell proliferation and angiogenesis [ 34 , 66 , 67 , 80 , 141 , 142 , 143 ]. In particular, SS-based antimicrobial materials are favorable for hemostasis through increasing the activity of FXIIa (the initiator of the coagulation cascade) and FIIa (the final thrombin in the coagulation cascade) [ 66 ].…”
Section: Figurementioning
confidence: 99%
“…The dressings also has anti-inflammatory properties through down-regulating pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-17 [ 144 ] as well as synthase enzymes involved in the inflammatory process, including COX-2 (cyclooxygenase) and iNOS (inducible nitric oxide synthase) [ 142 ] and increasing the anti-inflammatory cytokine IL-10 [ 141 ]. Inhibition of pathogenic bacteria will increase growth factor secretion and further promote cell proliferation, migration and angiogenesis [ 34 , 143 ].…”
Section: Figurementioning
confidence: 99%